Evaluación de la influencia de la taralla de maíz (Zea mays) en la obtención de papel ecológico - Chang Sánchez, Gema Nataly (2019)
The research focuses on obtaining ecological paper from the corn stem (Zea mays) as a solution to reduce deforestation and reduce lignocellulosic residues. For the development of the experiment, the proportion of the residue was considered as a variation factor having 4 levels such as: (25%, 50%, 75%,100%), these being the treatments, with four replications each, using the InfoStat software (2018) the analysis of the results was performed. In obtaining the pulp, a semi-chemical process was used, ideal for non-wood fibers, obtaining sheets of paper of 30 cm x 24 cm with a total of 16 experimental units, divided into 8 parts with dimensions of 7.5 cm x 12 cm each sheet for the analysis of physical properties (grammage, thickness and% humidity) according to TAPPI Standards T 410, 411, 412. Finally, a paper was obtained that meets the required conditions, with a residue amount of 50 %, whose characteristics were: a thickness of 0.75 mm, a weight of 115 g / m2 and a percentage of humidity of 6.70%, the hypothesis raised is confirmed with the results of the second treatment and through the unit price analysis the cost per dozen paper was obtained and the profit was added which was 15% resulting in $3.69 price accessible to the market.